Development of Brand Community in Iranian New Sport Teams - Amin Rayat; Mehdi Rayat; Layla Rayat (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Through years of spectator interaction, historical moments, heroic performances, and the creation of traditions or rituals, these established teams are excellent examples of brand communities. For newly introduced teams, these elements are likely to be in short supply and many of them struggle to build a community around their sport team. Objectives. This study explored brand community markers in the context of newly established sport teams. Methods. We examined whether managers of new sports teams Utilize group experience, organizational history, ritual/traditions and physical facility in their branding strategies. A case study approach was used; featuring both interviews with managers of three newly established Iran professional sports teams and direct observations of games. Results. The findings revealed managers generally considered group experience, history and heritage, ritual/traditions and physical facility to be important, but they failed to implement and apply these mechanisms to an overall marketing strategy. Evidence of the four mechanisms was only apparent on an infrequent and fragmented basis. Promotion of these antecedents was largely absent from the team's branding strategies. Conclusion. This is the first study to extend the study of brand communities from successful and established brands to new organizations and explored how the different mechanisms relate to this.